Evaluation of Judicial Practices by Students of the Faculty of Syari’ah Padang State Islamic University in the West Sumatra Religious Courts - Masna Yunita; Fitra Nelli (LEGAL BRIEF, 2022)
Judicial practice is one of the compulsory subjects for the Syari'ah Faculty of UIN Imam Bonjol Padang which is held in the West Sumatra Religious Court. There are 18 religious courts in West Sumatra, while the number of students from the shari'ah faculty continues to grow from year to year. In order to improve practical activities, it is necessary to conduct an evaluation of student justice practices so far. To obtain data, interviews were conducted with judges, clerks for practicing supervisors, as well as with students who had practiced. Based on the research, it can be concluded that practical problems arise from internal problems and external problems. One of the most important problems is that when new students come to court, it appears that the students are unprepared and do not understand the procedural law of religious courts. even though they have received supplies. So it is necessary to conduct a further evaluation of the activities of debriefing students' judicial practices.